2014
DOI: 10.5194/bgd-11-2189-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can a bog drained for forestry be a stronger carbon sink than a natural bog forest?

Abstract: Abstract. This study compares the CO2 exchange of a natural bog forest, and of a bog drained for forestry in the pre-alpine region of southern Germany. The sites are separated by only ten kilometers, they share the same formation history and are exposed to the same climate and weather conditions. In contrast, they differ in land use history: at the Schechenfilz site a natural bog-pine forest (Pinus mugo rotundata) grows on an undisturbed, about 5 m thick peat layer; at Mooseurach a planted spruce forest (Picea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…At the SPRUCE study site, using a unique collar enclosure method (1.13 m 2 ) that excluded trees (but likely not tree roots) Hanson et al [] reported annual NEE ranging from a slight sink of −3.1 g C m −2 yr −1 in 2013 to a C source ranging from 21 to 65 g C m −2 yr −1 across 2011, 2012, and 2014 (our main year of measurement). Annual net CO 2 exchange for temperate bogs typically ranges from slight sources (10 g C m −2 yr −1 ) to slight sinks (−76 g C m −2 yr −1 ) depending on bog site and the variable environmental conditions including water table, snow cover, and day and nighttime temperatures [ Lafleur et al ., ; Sottocornola and Kiely , ; Hommeltenberg et al ., ; Hurkuck et al ., ].…”
Section: Discussionmentioning
confidence: 98%
“…At the SPRUCE study site, using a unique collar enclosure method (1.13 m 2 ) that excluded trees (but likely not tree roots) Hanson et al [] reported annual NEE ranging from a slight sink of −3.1 g C m −2 yr −1 in 2013 to a C source ranging from 21 to 65 g C m −2 yr −1 across 2011, 2012, and 2014 (our main year of measurement). Annual net CO 2 exchange for temperate bogs typically ranges from slight sources (10 g C m −2 yr −1 ) to slight sinks (−76 g C m −2 yr −1 ) depending on bog site and the variable environmental conditions including water table, snow cover, and day and nighttime temperatures [ Lafleur et al ., ; Sottocornola and Kiely , ; Hommeltenberg et al ., ; Hurkuck et al ., ].…”
Section: Discussionmentioning
confidence: 98%
“…The bog has a 5‐ to 6‐m‐thick peat layer mainly under permanently water‐saturated conditions. The peat substrate and current vegetation is dominated by sphagnum mosses, with spatially variable contributions of sedges, heather meadows, and bog pines (Hommeltenberg et al, 2014). Vegetation around the south monitoring well is only sphagnum moss.…”
Section: Model Applicationmentioning
confidence: 99%
“…The northern part of the bog was partly affected by peat cutting until the 1950s (Hommeltenberg et al, 2014). Because the peat cutting occurred only in parts, the peat layer is spatially variable, showing different stages of decomposition.…”
Section: Model Applicationmentioning
confidence: 99%
“…Many more studies have quantified NEE for peatlands, but not aquatic carbon export, i.e., in subarctic (Aurela et al 2002;Lund et al 2015), boreal (Aurela et al 2007(Aurela et al , 2009Peichl et al 2014;Sagerfors et al 2008), tropical (Hirano et al 2012;Mezbahuddin et al 2014), and temperate peatlands (Beetz et al 2013;Campbell et al 2014;Elsgaard et al 2012;Lund et al 2007;McVeigh et al 2014). Despite the lack of quantification of key components of NECB, several studies claimed to quantify the carbon sink strength of these peatlands (Campbell et al 2014;Hirano et al 2012;Hommeltenberg et al 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%